2021
DOI: 10.5194/wes-2021-79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical wake deflection for floating wind turbines by differential ballast control

Abstract: Abstract. This paper presents a feasibility analysis of vertical wake steering for floating turbines by differential ballast control. This new concept is based on the idea of pitching the floater with respect to the water surface, thereby achieving a desired tilt of the turbine rotor disk. The pitch attitude is controlled by moving water ballast among the columns of the floater. This study considers the application of differential ballast control to a conceptual 10 MW wind turbine installed on two platforms, d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…From Figure 7, for the below-rated wind speed scenario, this center is half a diameter higher than the hub height, which implies that the wake deflects upwards. This phenomenon has been previously observed by Wise and Bachynski, 19 Doubrawa et al, 51 and Nanos et al, 52 for below-rated wind speeds. The reason behind this deflection is the non-zero vertical component of the thrust that the incoming flow experiences when encountering a rotor with a specific tilt with respect to the ground.…”
Section: Results On Deficit and Meanderingsupporting
confidence: 80%
“…From Figure 7, for the below-rated wind speed scenario, this center is half a diameter higher than the hub height, which implies that the wake deflects upwards. This phenomenon has been previously observed by Wise and Bachynski, 19 Doubrawa et al, 51 and Nanos et al, 52 for below-rated wind speeds. The reason behind this deflection is the non-zero vertical component of the thrust that the incoming flow experiences when encountering a rotor with a specific tilt with respect to the ground.…”
Section: Results On Deficit and Meanderingsupporting
confidence: 80%
“…Finally, regarding the impact of the motion of the floater on the wake characteristics, the amplitude of the surge and sway motions used in this study was relatively small compared to the values used in numerical (Nanos et al, 2021;Chen et al, 2022) and wind tunnel (Fu et al, 2019;Schliffke et al, 2020) studies that focused on the study of the effect of the wind turbine motion on the wake characteristics. Comparing the standard deviation of the surge motion speed with the longitudinal speed showed that the standard deviation of the wind was one order of magnitude larger.…”
Section: Discussionmentioning
confidence: 96%
“…In the case of floating wind turbines, the wind turbine motion that results from the interaction of the floating structure with the wind and sea has to be considered, in addition to the atmospheric conditions. The wake characteristics of floating wind turbines have been studied using numerical (Wise and Bachynski, 2020;Kleine et al, 2021;Nanos et al, 2021;Chen et al, 2022;Li et al, 2022) and wind tunnel (Fu et al, 2019;Schliffke et al, 2020) experiments. Those studies focussed on the impact of the sway (Fu et al, 2019;Nanos et al, 2021;Li et al, 2022), surge (Fu et al, 2019;Schliffke et al, 2020;Chen et al, 2022) and heave (Kleine et al, 2021) motions on the turbine operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical and horizontal deflection are a consequence of the built-in shaft tilt (referred to as shaft tilt in the following) and vertical shear, and yaw misalignment, respectively. For floating wind turbines (FWTs), and specifically for low wind speed conditions, several authors [1][2][3] have reported the deflection of the wake not only because of the FWT shaft tilt, but also due to the platform pitch angle. This phenomenon, combined with the variation in the projected area of the rotor, affects both the produced power and the loads of the FWT in the wake.…”
Section: Introductionmentioning
confidence: 99%